The politics of naming a movement independent cinema according to the Cinemalaya Congress (2005-2010) - Campos, Patrick F. (Philippine humanities review = Rebyu ng Arte at Literatura ng Pilipinas.)
"...Patrick F. Campos had the opportunity to dissect the politics of various independent film organizations and the assumptions of the different theoretical frameworks used by the critics who joined the congress. Campos's experiences serve as the basis of his essay, which teases out both the politics in naming the "indie film movement" in the Philippines and the discourses that have contributed to what it means to be "independent" in Philippine cinema." -- Introduction